Effects of Adding Vermicompost to the Tort-Perlite Mixture on The Development of Pepper Seedlings - Sezer Şahin (Turkish Journal of Agriculture: Food Science and Technology, 2020)
The aim of this study was to determine the effects of vermicompost application on the growth of pepper seedlings. Fertilizer doses and application time applied to plants are among the most important factors affecting seedling quality in seedling production. Vermicompost products have many advantages from plant development to soil regulating effects, antioxidant effect and the use of all kinds of wastes (plant, animal, industrial, etc.) in production. Seedling mortar (70% peat and 30% perlite), which was constituted in the study, constituted the control group of the study. Pepper seedlings were grown by adding different doses of vermicompost (5, 10, 20%) to this control group. The properties of the vermicompost used were pH: 7.5, EC: 2.15 dS m-1, C / N: 18.71, organic matter: 64%, N: 1.25%, K2O: 1.02%, P2O5: 0.55 %). In the study, full fertilizer (EC: 1) dose and semi fertilizer (EC: 2) dose were applied in fertilization. Köylüm pepper varieties was used in the study. Total output rate (%), stem length (cm), stem diameter (mm), number of leaves (number), stem length (cm), wet and dry leaf weight (g), wet and dry body weight (g), wet and dry root weight (g) properties were determined. According to the control group, 10 and 20% vermicompost application of pepper seedlings wet weight, dry body weights and wet and dry root dry weights were statistically increased. The first emergence of plant seedlings and their marketable times were withdrawn early by vermicompost application. At the end of the study, it was determined that some of the properties examined with vermicompost application to control mortar increased. Vermicompost application showed good performance in working as an organic fertilizer that can be mixed with peat and perlite mixture.